Finding the Principle Leads using GC-MS and Unravelling the Anti-inflammatory Activity of Alkaloid Isolated from Caesalpinia bonducella by in vitro Techniques - Mathiyazhagan, Sandhiya; Yadav, Hrishita; Vishwanathan, Ramya; Reddy, Amala (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim/Background: Plant-based medicines have gained remarkable recognition recently, as consumers have begun to express their preference for herbal remedies. C. bonducella, commonly known as fever nut, is said to have massive value in Ayurveda regarding health and cosmetics. We aim to envisage the alkaloid for its anti-inflammatory property using in-vitro techniques. Materials and Methods: C. bonducella powder, soxhlet apparatus, solvents including hexane, DCM, ethyl acetate and methanol. GC-MS, L929 cells, DMEM medium, antibiotic solution, sulfanilamide, naphthylethylenediamine, phosphoric acid, ferric chloride, sodium hydroxide, potassium iodide and ammonium hydroxide. Results: The cell-free in-vitro anti-inflammatory assay showed 75% Membrane Stabilization, 125% Albumin denaturation assay and 106% Proteinase inhibition assay at 1mg/mL of aqueous extract. The cell viability remained unaltered even in the highest tested concentration, with a dose-dependent nitrite inhibition count recorded. Conclusion: Alkaloids, carbohydrates and flavonoids showed their presence in aqueous solution of seed powder. This study showed that the isolated alkaloids found to be in higher concentration in Aqueous extract and subsequently employs GC-MS to understand the various compounds present in it. The attenuation of pro-inflammatory mediator Nitric oxide was significant in Aqueous extract which supports the anti-inflammatory potential of the extract.
Keywords: Caesalpinia bonducella; Fever nut seeds; GC-MS; Anti-inflammatory; Alkaloid